Методи та інструментальні засоби планування Wi-Fi мереж - Бондар, С. О. (ХНУРЕ, 2024)
The research topic is devoted to methods and tools for planning Wi-Fi networks. In the context of the rapid development of wireless technologies, especially Wi-Fi, there is a need for effective network planning to ensure the highest level of performance and reliability. The article analyzes various Wi-Fi network planning methods, including analytical and computational approaches. In addition, modern tools designed to automate the planning process, such as software packages and services using artificial intelligence algorithms, are discussed. Highlights the advantages and disadvantages of various Wi-Fi network planning methods and tools, as well as their potential applications in real-world scenarios.
Keywords: планування Wi-Fi мереж; Wi-Fi мережа